The Role Motivation to Overcome Fossilization in Pandemic Era - Hayati, Asmul (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
Fossilization became a hot topic following Selinker’s (1984) prediction that 95% of second language students would never gain native-like control of the chosen language. Although the exact causes are unknown, numerous experts have suggested that a lack of drive could be one of them. This study aims to know the role of motivation to overcome fossilization at SMAN 2 Tapung. The researcher believes that motivation has a big role to overcome fossilization in learning English as a foreign language. This study used descriptive qualitative research. The data were collected by using an open-ended questionnaire. Meanwhile, there are two participants in this research. The result showed that, students still have some difficulties in learning English and motivation also has a big role to overcome fossilization.